[PP.19.33] INVASIVE AORTIC PRESSURES IN AN ARAB POPULATION- IMPACT OF AGE & GENDER. (September 2017) - Mahmud, A.; Balgith, M.; Ayoub, K.; Khan, F.; Samir, M.; Thanoon, B.; Shabeeb, A. Al; Ghamdi, M.A.
Abstract : Objective: While pulsatile hemodynamics is well-established as independent prognosticator in various ethnic populations, currently there are no data on these important measures in an Arab cohort. Methods: We performed retrospective analyses on invasive central aortic and simultaneously measured non-invasive brachial pressures in some 2900 patients referred for coronary angiography to the Cardiac Catheterization Laboratory at King Abdul Aziz Cardiac Center, King Abdul Aziz Medical City, Riyadh, Saudi Arabia between the years 2010 and 2016. We stratified the central systolic, pulse pressure and pulse pressure amplification by brachial blood pressure categories, age and gender. Results were analysed with JMP, version 7.1 (SAS for Windows), p < 0.05 considered significant. Design and method: The mean age of the population was 59 ± 11 years, 23% female. There was a significant linear relationship between age, central systolic (r = 0.29, p < 0.0001), diastolic (r = −0.30, p < 0.0001) and pulse pressure (r = 0.45, p < 0.0001). The mean pulse pressure amplification was −5 ± 18 mm Hg with significantly lower values in women than men (−10 ± 22 vs. −3 ± 15, p < 0.0001). Central pulse pressure and PP amplification increased linearly with age in both genders until the age of 60 years, after which there was a plateauing effect (p < 0.0001). However, the increase in central pulse pressure with age was steeper in women than men (p < 0.001). Conclusions: This is the first study describing invasive pulsatile haemodynamic patterns in coronary artery disease patients of Arab descent. The results show reduced pulse pressure amplification values compared with Caucasian data, although gender and age relationships are generally similar in our cohort. Our study also shows women to exhibit an accelerated increase in aortic pressures with age compared with men which may explain the worse outcome in females as observed in acute coronary syndrome registries.